Percutaneous Fixation without Bone Graft for Scaphoid Nonunion - João Carlos Belloti; Klebson Bruno Lopes Vasconcelos; Jorge Raduan Neto; Aldo Okamura; Marcela Fernandes; Vinícius Ynoe de Moraes (Revista Brasileira de Ortopedia, 2021)
Abstract Objective To describe the clinical and radiographic outcomes of patients submitted to percutaneous fixation without bone graft for scaphoid nonunion, with a minimum follow-up of six months. Methods A case series study of a convenience sample of hand surgeons with prospective evaluation. Patients with scaphoid (waist or proximal pole) nonunion and the following features were included: more than six months of history; X-rays showing sclerosis of the edges of the nonunion, with resorption of the nonunion focus measuring less than 4 mm (Slade & Gleissler I, II, III and IV) and no angular deformity; and no proximal pole necrosis on magnetic resonance imaging (MRI). Results After six months of follow-up, all nonunion were consolidated, with no major complications. The functional outcomes revealed good scores on the disabilities of the arm, shoulder and hand (DASH; n = 12; mean: 6.9; standard deviation [SD]: 2.1) and patient-rated wrist evaluation (PRWE; n = 12; mean: 7.97, SD: 1.5) questionnaires. The results of the visual analog scale (VAS) showed little residual pain (n = 12; mean: 0.71; SD: 0.2). Slight decreases in flexion (69 versus 59.1; p = 0.007), extension (62.4 versus 48.7; p = 0.001) and radial deviation (29.6 versus 24.6; p = 0.014) were detected in comparison to the contralateral side. Conclusions All cases in the series presented consolidation and good functional scores at the six-month evaluation. This is a promising option (with lower technical demand and morbidity) for the treatment of scaphoid nonunion. Comparative studies are required to assess the effectiveness of this technique in comparison with other options.